Floral advertisement scent in a changing plant-pollinators market - Filella, Iolanda; Primante, Clara; Llusià, Joan; Martín González, Ana M.; Seco, Roger; Farré-Armengol, Gerard; Rodrigo, Anselm; Bosch, Jordi; Peñuelas, Josep (Scientific reports, 2013)
Plant-pollinator systems may be considered as biological markets in which pollinators choose between different flowers that advertise their nectar/pollen rewards. Although expected to play a major role in structuring plant-pollinator interactions, community-wide patterns of flower scent signals remain largely unexplored. Here we show for the first time that scent advertisement is higher in plant species that bloom early in the flowering period when pollinators are scarce relative to flowers than in species blooming later in the season when there is a surplus of pollinators relative to flowers. We also show that less abundant flowering species that may compete with dominant species for pollinator visitation early in the flowering period emit much higher proportions of the generalist attractant β-ocimene. Overall, we provide a first community-wide description of the key role of seasonal dynamics of plant-specific flower scent emissions and reveal the coexistence of contrasting plant signaling strategies in a plant-pollinator market.